Georges Vanier - Bertrand, Luc (LIDEC, 1993)
Les diverses étapes de la prestigieuse carrière de cet ancien gouverneur général du Canada.

Joseph-Adolphe Chapleau - Bertrand, Luc (LIDEC, 1994)

Honoré Mercier - Bertrand, Luc (LIDEC, 1994)